PENGARUH LEVERAGE, GROWTH OPPORTUNITIES DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI (Studi Pada Perusahaan Keuangan Dan Perbankan Di Bursa Efek Indonesia Tahun 2013-2015) - Erika Anantya Rahmawati, 13.05.52.0132; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
The study examines the effect of Leverage, Growth Opportunities and Firm Size on conservatism in accounting. This reserch was conducted at the finance and banking companies listed on the Indonesia Stock Exchange.Â The sampling method used purposive sampling with the observation period from 2013 to 2015. Relationship and (or) influence between variable is described by using multiple regression analysis. The result indicted that 1) Leverage had insignificant negative 2) Growth Opportunities had insignificant negative and 3) Firm Size had a negative significantly effect on accounting conservatism on finance and banking company listed on the Indonesia Stock Exchange in the period 2013-2015.Keywords: Leverage, Growth Opportunities, Firm Size and Conservatism in Accounting